Is there an Aesthetics in Golden Ratio as Regards to the Common CIS-Regulatory Elements and GC (G) Guanine (C) Cytosine / AT (A) Adenine (T) Thymine Base Pairs? - Ölmez, Tahir (Selected Topics in Humanities and Social Sciences Vol. 9, 2022)
One of the modern organization theories is “systems approach theory”. General systems theory has many sustainable relationships between many varied sciences. Depending on many sciences, from chemistry and mathematics to biology, many syntheses can be obtained from these connected relationships. Not only atoms with the smallest structures of bases [Carbon(C), Nitrogen (N), Oxygen (O) and Hydrogen (H)], but also the root numbers of golden ratio after comma (1, 618034…) can be taken as a small unit for evaluating analysis from genetic algorithms. So, this paper attempts to investigate not only the relationship between golden ratio numbers “618” and Adenine Thymine (AT) base pairs / Guanine Cytosine (GC) base pairs molar masses, but also the relationship between golden ratio numbers and both the average of TATA box nucleotides and CAAT box nucleotide bases sequence on the basis of molar masses. Firstly, the molar mass of (GC) base pairs “618” is the same value of golden ratio numbers after comma (1, 618034…). Secondly, the value of “608” in calculation of TATA Box gene sequence and ‘602’ in calculation of CAAT Box gene sequence, almost the same as the first three digits “618” of golden ratio after the comma (1,618).Thirdly, after searching the CAAT box gene sequence “GGCCAATCT” and the TATA box gene sequence “TATAAAA” in the NCBI (National Center for Biotechnology) databases, NCBI blast results of TATA and CAAT Box were specifically focused on a variety of bony fishes especially 'Denticle herring’. In sum, after calculating total atomic numbers of each TATA and CAAT Box, the numeric values of these results have values close to the numerical value of "618", which are almost the same as the first three digits “618” of golden ratio after the comma (1,618).